Corrigendum to “Tegula atra (Lesson, 1830) (Mollusca, Gastropoda) in the marine Quaternary of Patagonia (Argentina, SW Atlantic): Biostratigraphical tool and palaeoclimate-palaeoceanographical signal” [Quat. Int. 305 (2013) 163e187] - Aguirre, Marina Laura (2013)
Fil: Aguirre, Marina Laura. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina